Leak detection in pipelines using wavelet and cepstrum analysis - Abdul Kadir, Samta (2013)
Nowadays, piping system is one of the important features in either home of industrial user. It is essential for transporting fluid from a point to another point. But due to many reasons, leaks may occur in the pipelines. This research is focusing on detecting and locating the leaks in the pipeline and to successfully complete the research signal analysis of wavelet and cepstrum analysis is used. This research proposed a technique which is transient method. The basic principle is the fact that water spouting out of a leak in a pressurized pipe generates signal, and this signal contains information to whether a leak exists and where it is located. The present transient methods for finding leaks are mainly based upon correlation analysis, where one sensing device is installed at each side of a leak. This method is hard to operate because it needs a lot of operators to operate it due to equipment in different place. So to overcome this limitation, this research project proposed a new method by using just one sensing device which means all of the equipment in one place. This method use pressure transducer as the sensing device. This will make the method more friendly user and reduce the cost of operators. The results predict satisfactorily the leak location as the error between analyzed data and measured data is from 0.81% to 4.26%. This report starts with the introduction section to outline on the backgroundn and purpose of the study. It continues with the literature section that explains theleakage detection techniques, wave propagation and signal processing. The experimental part involves fabricating the pipe system using high density polyethylene and galvanized iron pipe. Subsequently signal processing section covers analysis of data and final results.